P–386 Uterine Natural Killer Cell function in Recurrent Miscarriage and Implantation Failure: A Systematic Review. (6th August 2021) - Greer, O; Woon, E V; Shah, N M; Johnson, M R; Male, V
Abstract: Study question: Does uterine natural killer cell functional activity differ in women with recurrent miscarriage (RM) or implantation failure (RIF) compared to fertile controls? Summary answer: There is insufficient data to conclusively determine differences in uterine natural killer (NK) cell activity between women with RM/RIF and controls. What is known already: Uterine NK cell (uNK) function is central to maintaining healthy pregnancy by promoting placentation and spiral artery vascular remodelling. The range of uNK activity is diverse and includes cytokine secretion, such as IFN-γ, or angiogenic factors which promote vascular remodelling. Despite an abundance of studies investigating peripheral blood NK cell cytotoxicity, there is limited evidence of uNK cytotoxicity. uNK-trophoblast interactions are facilitated by uNK receptors such as CD94, LILRB1 and KIRs. It is possible that dysfunction of these diverse uNK activities plays a more important role in early pregnancy failure than uNK levels. Study design, size, duration: We conducted a systematic review of prospective case-control studies investigating uterine natural killer cell activity in patients with RM or RIF versus controls. The aim was to determine whether there was a distinct variation in uNK activity between RM/RIF and controls. We stratified uNK activity into four broad categories: i) regulation and receptors; ii) cytotoxicity; iii) expression of cytokines; iv) effect on uterine vasculature. Participants/materials, setting, methods: The electronic database search included MEDLINE, EMBASE, Web of Science and bibliographies from included articles from inception to December 2020 using a combination of MESH and keywords. Search, screen, and data extraction were performed by two reviewers independently. Quality assessment was conducted with ROBINS-I. Out of 4636 studies screened, 30 studies (1696 women) were analysed for uNK activity. Main results and the role of chance: Different methods were used to measure uNK activity including immunohistochemistry, flow cytometry, ELISA, PCR and Western blot. Samples were obtained from endometrium during mid-luteal phase or decidua following surgery. 14 studies reported on uNK phenotypes associated with regulation and receptors. RM/RIF patients, compared to controls, demonstrated a reduced expression of KIR2DL4, KIR2DL3/L2/S2 and inhibitory receptors (NKG2A); whereas there was a higher expression of the activating receptor (NKp46) and CD161. One study reported correlation between FoxP3+ T-cells and CD56+ NK cells but another reported no similar correlation with CD57+/CD56+ ratio. Two studies investigating dNK cytotoxicity, using chromium release or lactate dehydrogenase release assays, concluded higher dNK cytotoxicity in RM patients. Eight studies reported on cytokine expression. Interestingly, two studies found lower expression of IFN-g, but four studies reported otherwise in RM patients. Two studies found a higher ratio of dNK producing IFN-γ/TNF-α to those producing IL–4. The rest of the studies reported lower expression of IL–1RA, IL–10, TNF-α, Lnc–49A and higher expression of granzyme B, perforin and PRF–1. Finally, six studies reported on effect of uNK on vasculature. Among the findings were negative correlation between CD16+ uNK and endometrial IL–6 and VEGF, as well as higher angiogenin, VEGF and bFGF expression. Limitations, reasons for caution: Functional activity investigated amongst studies varied significantly; this heterogeneity precluded meta-analysis of the data. Heterogeneity also prohibited definitive conclusions on uNK function and pregnancy outcome. Studies presented data in a combination of qualitative and quantitative analysis and variation was seen in the criteria for inclusion of RM, RIF and controls. Wider implications of the findings: uNK levels alone may be insufficient to guide management of early pregnancy failure. Clarification of underlying functional activity may guide therapeutic intervention and help develop new treatments. This review highlights the need for a greater understanding of the role of uNK activity in healthy pregnancy and early pregnancy failure. Trial registration number: N/A